Peran Rotasi Kerja Terhadap Kinerja Pegawai - Dewi Untari; Wendy Muliadi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Performance measurement of public sector employees that are oriented to results (output) is not just assessment (input) and (output) only, the process of discussing progress related to the achievement of predetermined goals and objectives so that this study aims to improve employment relations of employee performance. This study is a descriptive study using data statistics derived from primary data. The method used in this study is descriptive statistics. The sample in this study amounted to 64 respondents. This research was conducted at Simed Prakarsa Indonesia. The results of the study show that the work rotation system that has been done well for the level of organizational performance is also in the good category, with a level of achievement at the level of closeness.